2022
DOI: 10.1111/jvh.13741
|View full text |Cite
|
Sign up to set email alerts
|

Severe impairment of patient‐reported outcomes in patients with chronic hepatitis C virus infection seen in real‐world practices across the world: Data from the global liver registry

Abstract: Cure of chronic hepatitis C (CHC) can lead to improvement of health-related quality of life and other patient-reported outcomes (PROs). While extensive PRO data for CHC patients who were enrolled in clinical trials are available, similar data for patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The study expands on recent findings that provided PROs by global region. Investigators found that the Middle East had lower PROs compared to other regions of the world, such as high‐income countries and Eastern Asia 8,9,17 . Herein, we have provided results demonstrating three countries may be impacted more by one CLD than another.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…The study expands on recent findings that provided PROs by global region. Investigators found that the Middle East had lower PROs compared to other regions of the world, such as high‐income countries and Eastern Asia 8,9,17 . Herein, we have provided results demonstrating three countries may be impacted more by one CLD than another.…”
Section: Discussionmentioning
confidence: 66%
“…Per the GLR protocol, each investigator willing to establish a GLR site within their country obtained approval to enrol and consent patients from their local Institutional Review Board (IRB) or a similar supervisory institution. Patients enrolled in GLR from participating sites were required to have CLD with a pre‐defined list of aetiologies: chronic hepatitis B (CHB), chronic hepatitis C (CHC) or NAFLD/NASH 8,9 . Excluded from GLR were patients who were younger than 18 years of age; had other causes of CLD (e.g., autoimmune or drug‐induced liver disease); excessive alcohol use defined as more than 14 drinks per week; had decompensated cirrhosis, HCC, and other liver malignancies; were post‐liver transplant; were pregnant; or were unwilling or unable to give informed consent.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, compared with clinical trial enrollees, patients in real-world practices were less commonly enrolled from high-income population, older, more commonly female, less employed, had more type 2 diabetes, anxiety and clinically overt fatigue but less cirrhosis. Sociodemographic confounders were the main reason of differences in HRQoL of HCV patients in different setting [ 7 ]. In longitudinal studies of DAAs treatment, utilities have also been shown to improve after treatment in patients with CHC in various settings.…”
Section: Discussionmentioning
confidence: 99%
“…Severe impairment of patient-reported outcomes (PROs) in patients with chronic HCV infection was seen in real-world practices across the world, while fatigue and psychiatric comorbidities were associated with significant PROs impairment in chronic hepatitis C (CHC) patients [ 7 ]. Besides, our previous study indicated health-related quality of life (HRQoL) of Chinese CHC patients was also impaired and associated with symptoms of discomfort, cirrhosis and depression [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preselected ELF cutoffs from the literature were used to assess sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV): 9.8 to rule out advanced fibrosis and 11.3 to rule in advanced fibrosis . To examine the validity of these rules in another external sample, the same calculations were performed in a nonoverlapping testing sample that included deidentified data from patients with biopsy-confirmed NASH enrolled in a previously described registry of our patients seen in other settings . Patients with and without advanced fibrosis from the registry for whom fib-4 and ELF scores were available were randomly sampled, with the prevalence of advanced fibrosis set similar to that seen in the original study sample.…”
Section: Methodsmentioning
confidence: 99%